2013
DOI: 10.1002/jcp.24461
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Activation of TRPC6 Channels in Rat Podocytes Requires Generation of Reactive Oxygen Species

Abstract: Angiotensin II (AII) plays a major role in the progression of chronic kidney diseases. Podocytes are essential components of the ultrafiltration apparatus, and are targets for AII signaling. AII has been shown to increase generation of reactive oxygen species (ROS) in podocytes. Canonical transient receptor potential-6 (TRPC6) channels stimulate Ca(2+) influx in podocytes, and have been implicated in glomerular disease. We observed that AII increased cationic currents in rat podocytes in an isolated glomerulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 51 publications
12
82
0
Order By: Relevance
“…7. Importantly, the effective concentrations of ANG II in our study were similar to those found by others and slightly higher with respect to those calculated in binding studies (1,16,32). Therefore, the effects observed are in line with pathophysiological concentration of ANG II in vivo, especially for autocrine/paracrine actions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…7. Importantly, the effective concentrations of ANG II in our study were similar to those found by others and slightly higher with respect to those calculated in binding studies (1,16,32). Therefore, the effects observed are in line with pathophysiological concentration of ANG II in vivo, especially for autocrine/paracrine actions.…”
Section: Discussionsupporting
confidence: 90%
“…The observed plateau effect on gCl by ANG II is also in line with a physiological and reversible activation of a G protein-coupled phosphorylation pathway. In addition, the present results add clear evidence that the production of ROS via NOX works as fundamental part of the pathway leading to the observed reduction of gCl by ANG II in myofibers as in other experimental conditions (1,41,43,73). This is emphasized by the observation that effects of ANG II are completely antagonized by both the classical antioxidant NAC and by the NOX inhibitor apocynin, as well as by the PKC inhibitor, although the occurrence of a parallel ROSmediated signaling cannot be fully ruled out.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this regard, PAN stimulates ROS generation in podocytes (45), and ROS potently activate TRPC6 (46,47). Moreover, Gq-coupled GPCRs stimulate TRPC6 activation, both directly through the second messengers DAG and possibly IP3 (1), as well as indirectly by stimulating ROS generation (48).…”
Section: 6mentioning
confidence: 99%